Outcomes Research in Perioperative Medicine. (14th May 2014) - Stundner, Ottokar; Memtsoudis, Stavros G.
Abstract : Outcomes research is emerging as an invaluable approach to the scientific evaluation of healthcare in a real-world rather than an experimental environment. There is much interest in the differential evaluation of existing interventions with regard to different patient populations. Moreover, various comorbid conditions necessitate analysis for the specific additional risk those factors convey in the perioperative arena, a task often difficult to accomplish without population-based techniques. The authors' group has conducted significant work in perioperative outcomes research utilizing CER and database analysis methodology, with focus on orthopedic surgery and anesthesiology. Our research resulted in numerous publications affecting policy and patient care over the last number of years. Knowledge on immediate perioperative outcomes of anesthesia and surgery is of very high interest not only to clinicians but also to administrators and policymakers, as it allows for risk assessment and allocation of resources. This review is not intended to be a systematic review but rather to (1) provide a brief overview over the theoretical basis of CER and population-based database research, (2) give an overview of our work with various points of focus, and (3) offer a perspective on the future development in perioperative medicine.